Phenolic Thiazoles with Antioxidant and Antiradical Activity. Synthesis, In Vitro Evaluation, Toxicity, Electrochemical Behavior, Quantum Studies and Antimicrobial Screening - Gabriel Marc; Anca Stana; Ana Horiana Franchini; Dan Cristian Vodnar; Gabriel Barta; Mihaela Tertiş; Iulia Şanta; Cecilia Cristea; Adrian Pîrnău; Alexandra Ciorîţă; Bogdan Dume; Vlad-Alexandru Toma; et al. (MDPI AG, 2021)
Oxidative stress represents the underlying cause of many chronic diseases in human; therefore, the development of potent antioxidant compounds for preventing or treating such conditions is useful. Starting from the good antioxidant and antiradical properties identified for the previously reported Dihydroxy-Phenyl-Thiazol-Hydrazinium chloride (DPTH), we synthesized a congeneric series of phenolic thiazoles. The radical scavenging activity, and the antioxidant and chelation potential were assessed in vitro, a series of quantum descriptors were calculated, and the electrochemical behavior of the synthesized compounds was studied to evaluate the impact on the antioxidant and antiradical activities. In addition, their antibacterial and antifungal properties were evaluated against seven aerobic bacterial strains and a strain of C. albicans, and their cytotoxicity was assessed in vitro. Compounds 5a-b, 7a-b and 8a-b presented remarkable antioxidant and antiradical properties, and compounds 5a-b, 7a and 8a displayed good Cu+2 chelating activity. Compounds 7a and 8a were very active against P. aeruginosa ATCC 27853 compared to norfloxacin, and proved less cytotoxic than ascorbic acid against the human keratinocyte cell line (HaCaT cells, CLS-300493). Several phenolic compounds from the synthesized series presented excellent antioxidant activity and notable anti-Pseudomonas potential.